PRACTICAL AND THEORETICAL PROBLEMS IN TEACHING ENGLISH (Conferencea, 2023)
This scientific article reveals practical and theoretical problems in teaching English. Consideration of the natural language environment as an important factor affecting the effectiveness of the educational process is considered a characteristic feature of the English language methodology as a solution to the main problems.